Manajemen Kinerja Berbasis Teknologi Digital: Peluang dan Tantangan di Perguruan Tinggi Kota Makassar - Kalla, Rastina; Tenriwaru; Syahnur, Muh. Haerdiansyah (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study explores how transformational leadership shapes team commitment and fosters loyalty and engagement among academic and administrative staff in higher education institutions in Makassar, Indonesia. Using a qualitative descriptive approach, data were collected through in-depth interviews, non-participant observations, and documentation at three selected universities. The findings reveal that transformational leaders—such as rectors, deans, and department heads—play a vital role not only as policy makers but also as role models, facilitators, and motivators. By clearly communicating the institution’s vision, encouraging open dialogue, and empowering team members, these leaders cultivate a strong emotional connection between individuals and the organization. Key strategies identified include entrusting staff with leadership roles in strategic projects, offering open and meaningful recognition, and creating a collaborative work environment. These approaches were shown to enhance intrinsic motivation, strengthen a sense of belonging, and build long-term organizational commitment. The study highlights the significance of human-centered leadership in navigating the complex challenges faced by today’s higher education institutions.